4(2n-3)+5n=

Simple and best practice solution for 4(2n-3)+5n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2n-3)+5n= equation:


Simplifying
4(2n + -3) + 5n = 0

Reorder the terms:
4(-3 + 2n) + 5n = 0
(-3 * 4 + 2n * 4) + 5n = 0
(-12 + 8n) + 5n = 0

Combine like terms: 8n + 5n = 13n
-12 + 13n = 0

Solving
-12 + 13n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 13n = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 13n = 0 + 12
13n = 0 + 12

Combine like terms: 0 + 12 = 12
13n = 12

Divide each side by '13'.
n = 0.9230769231

Simplifying
n = 0.9230769231

See similar equations:

| 1/4t=-400 | | 9r=-7.65 | | 4b-6-8b-4= | | 2x-5(3-2x)=5 | | x(3x-2)+x(2x-7)=(5x+3)(x-6) | | -23b=20.7 | | 9y-4y-2y=5 | | y=-3x^2+3x+18 | | 3t-5t=6 | | 8d=4/5 | | 24/x=12/50 | | 6-5y=1 | | 97=-3+5(5-3x) | | (7-v)(3v-2)=0 | | (98x+61y)/1.84=80 | | 5a+6b=140 | | 2-2t-4x=2 | | 6p+7p=-13 | | 9+3j=22 | | 6y+3x=8 | | 6v=-13 | | 56-5h=34 | | 4(8x^2-5)-[6(4x^2-5)+3]= | | 156=3(6w-9) | | 12+6n=84 | | 4x-2[6-(7-4x)]= | | 3.2y-9-5y+4.8x=5.7x | | Xy+x=-3 | | 5(8y-6)-(7y+5)= | | 9x-5x-6x=7x | | 9(3y-9)-(2y+7)= | | 7x+2(x-2)=9x+12 |

Equations solver categories